Investigating inflation persistence across monetary regimes - Luca Benati (European Central Bank (ECB), 2008)
Under inflation targeting inflation exhibits negative serial correlation in the United Kingdom, and little or no persistence in Canada, Sweden and New Zealand, and estimates of the indexation parameter in hybrid New Keynesian Phillips curves are either equal to zero, or very low, in all countries. Analogous results hold for the Euro area–and for France, Germany, and Italy–under European Monetary Union; for Switzerland under the new monetary regime; and for the United States, the United Kingdom and Sweden under the Gold Standard: under stable monetary regimes with clearly defined nominal anchors, inflation appears to be (nearly) purely forward-looking, so that no mechanism introducing backward-looking components is necessary to fit the data. These results question the notion that the intrinsic inflation persistence found in post-WWII U.S. data–captured, in hybrid New Keynesian Phillips curves, by a significant extent of backward-looking indexation–is structural in the sense of Lucas (1976), and suggest that building inflation persistence into macroeconomic models as a structural feature is potentially misleading.
Keywords: E31; E42; E47; E52; E58; 330; European Monetary Union; Gold Standard; inflation; inflation targeting; Lucas Critique; Markov chain Monte Carlo; median-unbiased estimation; Inflationssteuerung; New-Keynesian Phillips Curve; Eurozone; Goldstandard; Neue klassische Makroökonomik; Schätztheorie; Markov-Kette; Monte-Carlo-Simulation; Industrieländer